About Simona Kontrimiene’s doctoral dissertation entitled “Relationship between Humanistic Spirituality and Parenting Experiences - Targamadzė, Vilija (Acta Paedagogica Vilnensia, 2019)
[text in Lithuanian]
Keywords: none